PPPUD on Zero Waste Balinese Cattle Raising in Tunas jati Farmer Group, Getasan Village, Petang District, Badung - Ni Ketut Etty Suwitari; Ni Made Yudiastari; Luh Suariani; I Gusti Agus Maha Putra Sanjaya; I Kadek Wira Parwata; I Wayan Richo Yasa (Asian Journal of Community Services, 2023)
The Regional Superior Product Development Program activities will be carried out at the Tunas Jati Livestock Farmer Group located in Banjar Kauh Getasan Village, Petang District, Badung Regency. This livestock farmer group is engaged in the business of raising Balinese cattle and has been in existence since 2018. The number of livestock owned in this group is 30 heads, with a total of 8 members. In Bali cattle farming, feed will always play an important role in producing good livestock productivity.  The problem partners face is their lack of knowledge about quality feed and their lack of ownership of superior greenery that can encourage better livestock productivity.  The solutions provided to partners are 1) the introduction or planting of superior forage fodder, 2) Making various applications of technology that can improve and preserve forage feed, and 3) Processing livestock waste into high-value products. The output target to be achieved is TTG Technology for processing and preserving forage feed.